Integrating analyses in mixed methods research - Bazeley, Patricia (Thousand Oaks, California Sage Publications, Ltd., 2018)
This title goes beyond mixed methods research design and data collection, providing a pragmatic discussion of the challenges of effectively integrating data to facilitate a more comprehensive and rigorous level of analysis.
A foundation for integrated analysis -- Mixed methods in context -- Planning for analysis -- Interpreting data -- Integrative analysis strategies -- Sequential integration: Analysis guiding design and further analysis -- Complementary analysis of varied data sources -- Analysing linked data: Seeking patterns and contrasts -- From codes and counts to content analysis and 'big data' -- Integration through data transformation 1: Qualitative data to statistical variables -- Integration through data transformation 2: Exploratory, blended, and narrative approaches -- Inherently mixed, hybrid methods -- Exploring dissonance and divergence -- From integrative analyses to warranted assertions and a coherent, negotiated account.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology; Research -- Methodology; Mixed methods research